Construction and initial validations of the major decision-making self-efficacy scale (MDMSES) for Chinese high school students - Jingwen Li; Yanan Zhang; Limei Gao; Zhihai Qiu; Yu Zhou; Ying Guo; Tong Hao; Yongyi Li; Yu Bian; Dandan Li; Chunyan Zhu (BMC Psychology)
Abstract Background Major decision-making self-efficacy (MDMSE) is an important indicator of students’ ability to make effective decisions in specialty selection. It has implications for students’ personal growth and career counselling interventions. While the previous MDMSES has been widely used in the context of China’s New College Entrance Examination reform, the increased choice of majors and advancement of career planning necessitate a new scale to assess high school students’ MDMSE levels. Methods Scale items were generated based on a literature review, student interviews, and expert reviews. Exploratory Factor Analysis and Confirmatory Factor Analysis were used to assess the appropriateness of the scale’s structure, and network analysis was used to calculate concurrent validity. Retest reliability was calculated to evaluate stability. Results The MDMSES contains 24 items with five factors (Information Acquisition, Decision Persistence, Self-Determination, Self-Evaluation, and Social Support). The results show that the scale has a good five-factor structure (χ2/df = 1.91, CFI = 0.92, TLI = 0.91, RMSEA = 0.05, and SRMR = 0.06), and the internal consistency reliability of the total scale is 0.91. Conclusion The scale development results satisfied the psychometric and statistical criteria, allowing the scale to be used as a means of detection to support intervention efforts for individuals with low MDMSE levels.